Transinformação V. 21, N, 1, (jan/abr) 2009 (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2011)
link de acesso ao número: http://revistas.puc-campinas.edu.br/transinfo/viewissue.php?id=21